Efforts to Improve Local Wisdom Culture and History Learning Outcomes with Problem Based Learning Methods in Senior High School - Joko Purwanto (HISTORIA : Jurnal Program Studi Pendidikan Sejarah, 2022)
The purpose of this study was to describe the culture local wisdom of the value of the history learning education using the Problem Based learning method in students. The research method use: observastion, documentation, and interviews. Data analisys techniciques used data reduction, data analisys, and drowing conclusions using the expected research results in this study describe the culture local wisdom the main of X IPA 4 students in this history learning using the Problem Based Learning method with the following results. Before cycle was an increase 72,8%. Cycle I at the first meeting and the second meeting there was an increase 90,8%. Cycle II at the first meeting and second meeting there was an increase 106,4%. Cycle III at the first meeting and second meeting was an increase 108,4%. Completeness studies before cycle there was an 13,33%, Cycle I there was an 53,33%, Cycle II there was an increase 73,33%. Cycle III there was an increase 96,66%. The conclusion in this study that Problem Based Learning method can increase culture local wisdom of the class X IPA 4 SMAN 6 Metro students.